Effect of morbidity on change in mid-upper arm circumference in children under five years of age A COHORT STUDY IN PURWOREJO, CENTRAL JAVA, INDONESIA - Soeroyo Machfudz (Paediatrica Indonesiana, 2001)
The objective of this study were to find out the effect of morbidity (diarrhoeal diseases /DD & acute respiratory infection/ARI) on mid-upper arm circumference (MUAC) in children uner five years of age and to evaluate the impact of potential confounding and effect modifying factors on association between morbidity and MUAC development i.e. socioeconomic status, living area and breast feeding. A cohort study was carried out to follow morbidity and MUAC development from February 1996 to January 1997, including home visits and examinations every 3 months, totally four times. Data were collected through interviews and MUAC was measured using standard non-stretchable plastic tape. This analysis was performed on 2708 individuals (45.3% of the total sample), where complete morbidity and MUAC information was available, DD and ARI prevalence was highest in the second half of infancy. The overall period prevalence of DD and ARI was 1.4 and 9.9%, respectively. There was a small, but significant negative effect of diarrhoea on change in MUAC among infants below one year in the rural area, less so in the urban area. In older children there was no association between morbidity and MUAC velocity. There was a small positive association between maternal education and MUAC development in both age groups. Diarrhoeal diseases, showed a negative influence on MUAC development in infancy. However, in this study MUAC development from 12 months and onwards was not influenced by the load of illness. MUAC seems to be less sensitive in reflecting the morbidity history of the child, as compared to other anthropometric measurements.